Immunoferment, Cytomorphological, Cytochemical Parameters of Fish as Ecological Indicators of Resistance to Helminthes, Passed by Fish-Eating Birds - A. Nefedova, S.; A. Korovushkin, A.; M. Tunikov, G.; A. Fedosova, O.; V. Yakunin, Yu.; V. Baryshev, r. (International Journal of Engineering and Technology, 2018)
A search for indicators reflecting resistance of fish to helminth infections passed by fish-eating birds has been carried out. A decrease in the concentration of lysozyme by 13.5 % and an increase in hemagglutinin by 7.7 % for the bighead carp (Hypophthalmichthys nobilis), 19.9 % and 7.4 % correspondingly for scaly carp (Cyprinus carpio) and 18.6 % and 11.4 %, respectively for white amur (Ctenopharyngodon idela) identify the fish at risk for the incidence of helminths of Trematoda class (Posthodiplostomum brevicaudatum and Diplostomum spathaceum) and Cestoidea class (Pseudophyllidea). The diffuse-gel method revealed that the dynamics of lysozyme marks resistance of fish to invasions. A decrease in lysozyme indices in the kidney of a bighead carp by 30.1 %, that of a scaly carp by 10.9 %, and that of a grass carp by 6.6 % is an indicator of a decrease in the resistance of the fish to helminths. The positive pool of polysaccharide granulation in the cytoplasm of fish lymphocytes detected by periodic acid Schiff reaction attributes them to the risk group for helminth infections passed by fish-eating birds. A dangerous tendency to decrease resistance to invasions is precipitation of large glycogen granules in lymphocytes of silver carp (up to 2.7 %), scaly carp (up to 2.4 %) and white amur (up to 2.9 %), as well as small polysaccharide inclusions up to 24 %, 54 % and 43 % respectively. Among cytomorphologic markers of fish resistance to helminth infections, an increase (2-4 times) in the number of lymphocytes with caudate nuclei, micronuclei, and chromosome aberrations of the dicentric type is benchmark.Â Â